Analysis of the Whole and Part Methods to Improve Students Learning Outcomes and Kinesthetic Ability in Basic Footbal - Arsil; Astuti, Yuni; Erianti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to analyze the effect of the whole and part methods on learning outcomes in basic football skills. This is a aquasi-experimental research with the simple random sampling method used to collect data from 44 people. The instruments used in this study were 1) football basic technical skills tests for quality, 2) the Verducci battery for quantity, and 3) physical fitness tests for kinesthetic skill. Data were quantitatively and descriptively analyzed and supported by using two-ways analysis of ANAVA followed by the Tuckey test. The results showed the following: (1) the learning outcomes in football’s basic technical skills of students taught by using the whole method are better than the part method, (2) There is an interaction between teaching and kinesthetic skills in the learning outcomes of students’ basic football skills, (3) students with high kinesthetic skills taught by the whole method show a better result than those taught by the part method, (4) students with low kinesthetic skills taught by the whole method show lower result than those taught by the part method.